Représentations de genre dans un manuel scolaire de mathématiques de première année du primaire au Québec - Lafay, Anne (Canadian Journal of Education/Revue canadienne de l’éducation, 2022)
Stereotypes about gender-based mathematical abilities have an impact on different aspects such as students’ expectations or their ability to achieve mathematical learning. Analyses of mathematics textbooks from various countries around the world showed a more or less marked inequality of representations between female and male characters. The objective of this article was to investigate gender representations in mathematics textbooks used in Quebec with the French-speakers. A manual for the first grade of primary school was analyzed: The illustrated characters were identified and classified according to an analysis grid (gender, associated mathematics activity, space on the page, physical appearance, etc.). The results showed a real desire for gender equality in terms of mathematics aspects, but some gender differences persist (example: physical appearance).